2016
DOI: 10.1038/srep32954
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in sperm from Duroc, Landrace and Yorkshire boars

Abstract: Sperm contain microRNAs (miRNAs), which may have roles in epigenetic control. Regarding phylogenetic relationships among various swine breeds, Yorkshire and Landrace, are considered phenotypically and genetically very similar, but distinctly different from Duroc. The objective of the present study was to compare abundance of boar sperm miRNAs in these three breeds. Overall, 252 prioritized miRNAs were investigated using real-time PCR; relative expression of miRNAs in sperm was similar in Yorkshire and Landrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…The sperm miRNA has been reported most extensively and identified in all mammal species examined, including humans, mice, rats, rabbits, bulls, pigs and stallions (Amanai et al 2006, Cornwall 2009, Krawetz et al 2011, Das et al 2013, Stowe et al 2014, Kasimanickam & Kastelic 2016. Recently, breed-specific differential expression of miRNAs in the pig sperm was detected using the real-time PCR (Kasimanickam & Kastelic 2016). We identified 148 and 321 miRNAs in pig ejaculated sperm and epididymal sperm respectively.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The sperm miRNA has been reported most extensively and identified in all mammal species examined, including humans, mice, rats, rabbits, bulls, pigs and stallions (Amanai et al 2006, Cornwall 2009, Krawetz et al 2011, Das et al 2013, Stowe et al 2014, Kasimanickam & Kastelic 2016. Recently, breed-specific differential expression of miRNAs in the pig sperm was detected using the real-time PCR (Kasimanickam & Kastelic 2016). We identified 148 and 321 miRNAs in pig ejaculated sperm and epididymal sperm respectively.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to mRNAs, the diversity of the population of the sperm RNAs has now been extended to several non-coding RNAs, including miRNAs, piRNAs (Amanai et al 2006, Krawetz et al 2011, Pantano et al 2015, endo-siRNAs , small RNAs derived from tRNA, rRNA, snRNA and snoRNA (Peng et al 2012) and lncRNA . The sperm miRNA has been reported most extensively and identified in all mammal species examined, including humans, mice, rats, rabbits, bulls, pigs and stallions (Amanai et al 2006, Cornwall 2009, Krawetz et al 2011, Das et al 2013, Stowe et al 2014, Kasimanickam & Kastelic 2016. Recently, breed-specific differential expression of miRNAs in the pig sperm was detected using the real-time PCR (Kasimanickam & Kastelic 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly the results from that study have shown 47%-52% of the miRNAs that has been detected in the wild type have been dysregulated in DICER and Drosha knockout sperm groups [87] indicating active transcription of miRNAs during spermatogenesis. Moreover, the importance of miRNAs in sperm synthesis and male infertility has been described by analyzing miRNA expression in sperm cells derived from prepubertally hemicastrated Yorkshire boars [88], Landrace and Duroc sperm [89]. On the other hand, altered expression of certain miRNAs could be associated with poor sperm quality and male infertility.…”
Section: The Role Of Mirnas In Male Gametogenesismentioning
confidence: 99%
“…As a class of endogenous small (~22 nucleotides) noncoding RNAs, miRNAs mediate post-transcriptional gene expression in animals and ne-tune the expression of approximately 30% of all mammalian protein-coding genes [4][5][6]. In addition, miRNAs regulate gene expressions not only at post-transcriptional levels but also at the transcriptional level by RNA-RNA interactions [7].…”
Section: Introductionmentioning
confidence: 99%